Aerospace Technologies and Applications for Dual Use. - Finocchio, Pietro; Prasad, Ramjee; Ruggieri, Marina (River Publishers, 2008)
The events occurred in the last years have shown how the threat related to both intentional and natural disasters could bring the civil and the military worlds closer in the conceivement and deployment of countermeasures as well as in the identification of effective strategies for enhancing the Planet safety and security. In this frame, the concept of dual use - the set of technologies and applications that can be exploited for both civil and military purposes - becomes a key-topic. In addition, the aerospace is a strategic building block in the deployment of a network centric environment that aims at the global protection of the mankind. Aerospace is also a natural environment for dual use: many of the related enabling technologies have been first developed for the military world and then applied to civil - including commercial - purposes. On September 12-14, 2007 an International Symposium has been held in Roma, Italy, joining the dual use approach with the aerospace technology: the international community has been gathered around the key-topic: aerospace technologies and applications for dual use. The event has called experts and operators from the military and civil community, belonging to industry, scientific and governmental institutions. The common aim was an effective convergence between the available and perspected technologies for the civil and military worlds as well as the conceivement of applications that can take the maximum benefit from the dual approach, optimizing the available economic resources. The Symposium has included invited-only contributions and an industrial panel. The main results of the Symposium, derived from key-note speeches, invited lectures, panel discussions and conclusions have created the starting material to develop this Edited Book. The book - the first on the topic - can be considered a milestone and a key-tool aimed at driving the industrial, scientific and institutional efforts of the international community to guarantee a pleasant and safe future to the whole Planet. Contents Preface, Acknowledgements PART 1 - Trends and Challenges in Aerospace Dual Use: 1 - Introduction : a Strategic Vision on Dual Use; 2 - The Security-related Perspective of the European Space Agency; 3 - Complex Systems for Dual Applications at the Italian Space Agency; 4 - Systems-of-Systems and Processes Key to Dual Use; 5 - Strategy to Enhance the Technological Aerospace District (DTA) Impact in the Global Dual Scenario; 6 - Technology Applications for Evolving Security Needs; 7 - Dual Use in GMES: Analysis of Strategy and Developments; 8 - Extending the Internet into Space. PART 2 - Dual Use Technologies: 9 - Assets and Technologies for Space-based Dual Use Systems; 10 - Electro-Optic Sensors for Dual Use Space and Airborne Applications; 11 - TETRA in Heterogeneous Networks; 12 - Trends of Enabling Technologies for Sensors, Systems and System of Systems; 13 - Optimisation of Flower Constellations for Dual Use; 14 - Dual Use Technology and Applications: the GALILEO Case Study; 15 - Italian Initiatives for Broadband Communications and Data Relay Satellite Systems; 16 - Future Trends of an Integrated Aero-Space System for Autonomous Unmanned Vehicle Missions; 17 - Electronic Defence Dual Use Technologies and Applications. PART 3 - Dual Use Applications: 18 - Remote Sensing for Civil and Security Applications; 19 - Innovative Satellite Applications for Navigation and Earth Observation; 20 - GALILEO: a System with a Dual Use Dimension; 21 - Convergence of Navigation and Communication (NavCom)towards 4G; 22 - Innovative Satellite Applications for Homeland Security; 23 - Meteorology in the Dual Use Perspective; 24 - Dual Use Applications of High Resolution Radar Imaging. PART 4 - Industry Outlook on Dual Use: 25 - A contribution from Rheinmetall; 26 - A contribution from European Satellite Navigation Industries: an overview of the Galileo Program; 27 - Dual-Use Technologies & Applications for Space Systems; 28 - E.